Jual Beli Hamster dalam Perspektif Ekonomi Islam: (Studi kasus di Pasar Hewan Selasaan Arosbaya Bangkalan) - Rahmat Rahmat (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2022)
the perfection of the Islamic religion in regulating all human activities makes its adherents feel easy and always have a basis in acting, including in terms of buying and selling, the principle that must be fulfilled in Islamic Economics is that there must be mutual pleasure so that both parties do not feel forced and disadvantaged In addition, the goods sold must be in accordance with the provisions of the Islamic economy, that is, they must be sacred, own, and must have clear benefits. This study examines and examines Hamster buying and selling practices in terms of the perspective of Islamic Economics. This research uses qualitative research. the results of this study can explain that buying and selling hamsters in accordance with the provisions of Islamic Economics because all the terms and conditions of sale and purchase are met.